JULIAN AYUQUE: NARRATIVITY AND CULTURAL CONFLICT - Plasencia Soto, Rommel (2012)
Article that reveals a writer whose subject is the landscape and history of the peoples of Huancavelica. Through this, restrear his literary genealogy and a comparison with the so-called Andean literature, tributary the memory and oral tradition.